Studies on engine fuel consumption measuring system based on virtual instrument technology - YE Sheng; HU Jie (浙江大学学报. 农业与生命科学版)
In view of the defect of the traditional measurement, this paper introduces a new engine fuel consumption measuring system developed using virtual instrument technology. Based on the previous engine test system, the new system described in this paper is evolved. An engine transient-fuel-consumption intelligent meter is included as an extra part, which is comprised of weight sensor, fuel tank, fuel-filling electromagnetic valve, and other fuel pipes. The signal output from the weight sensor is transmitted to one of the analog channels of PCI-6024E board by conditioning circuit. The control signal of the electromagnetic valve is sent out from one of the digital channels of the PCI-6024E board, and the fuel pathway is switched from fuel-filling state to measuring state or vice versa. The design idea of the transient-fuel-consumption meter is based on the weightlessness principle and instantaneous flow survey conception, so the system can not only measure the fuel consumption with high accuracy, but also display the real-time instantaneous fuel flow and mean fuel flow. Using the Lab VIEW, the engine test system has been integrated with this transient-fuel-consumption meter, so it can show the real-time wave of rotation speed, torque and power during the testing phase, and get a continuous curve reflecting the change in real-time rotation speed, torque, power offering and instantaneous fuel consumption rate during variable work condition test.